(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Many biotic and abiotic stresses can be experienced by plants because they are sedentary organisms, which can stunt their growth and result in significant yield losses. For instance, plants are more stressed by the combination of drought and root-infecting pathogens than by either stress alone. While much is known about the modifications to metabolism, chemical technology, and body structure that occur in Fabaceae plants when they are young, little is known about how plants react to multiple stresses when subjected to single stresses. This is crucial for developing genetic propagation strategies that obtain a high and consistent yield within the subject while retaining equilibrium with plant defence reaction mechanisms. More research is needed to fully comprehend how legume plants identify and react to combinations of stress signals that occur simultaneously or sequentially for launching a range of adaptive responses.